Czech-Polish pilgrim songs in broadside ballads of 18th and 19th century - Szturcová, Monika (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
The paper constitutes an analysis of Czech-Polish relations in the Polish- and Czech-language pilgrim songs in the 18th-19th century. The main subject of the analysis is the select choice of pilgrim songs transferred from the Czech cultural context to the Polish and vice versa. The discussed texts allow the author to present new perspectives on possible research on broadside ballads and formulate a general approach to studying Polish-Czech culture transfer.